Caracterização de fisioterapeutas no sistema de saúde brasileiro - Costa, Larissa Riani (Universidade Federal de São Carlos, 2012)
Physical therapy appears worldwide in the late nineteenth century, being the first physiotherapy service installed in Brazil in 1884. In 1969, the profession is regulated by Decree-Law No. 938 and the following year the number of physiotherapists totaled 700 with six undergraduate courses. In 2011, the total number of physiotherapists registered in the Federal Council of Physical Therapy and Occupational Therapy (COFFITO) has reached 154,563 professionals, there are 542 undergraduate courses. The growing number of professionals, however, is not necessarily linked to the expansion of physical therapy for the population equitably. The present study aimed to investigate the distribution and role of physiotherapists in the health system, in order to contribute to policies and interventions according needs of the population, consisting of four articles. The first three articles aimed to describe the distribution of physiotherapists in the health system according to data provided by National Register of Health Service Providers (CNES), considering the different regions, federal units, and population size of cities, public and private sectors, and the different levels complexity of health care. The studies were characterized as descriptive cross-sectional studies, developed from data collected on the bank of CNES in Brasilia, referring to February 2010, and Census for 2010, and analyzed using descriptive statistics. Results: The study identified 53,181 registries of physiotherapists distributed of 22,238 establishments, arranged in 76% of the cities. Approximately 50% of registries were concentrated in the Southeast, 21% Northeast 18% South, Central-West 7% and 4% North. South and Southeast had the best ratio physiotherapists/1000 inhabitants (0.33 and 0.35, respectively), as opposed to the North (0.13), and the highest percentage of municipalities with registries (91% Southeast and 83% South), being observed in the North only 40% of cities with this type of professional. Metropolises and big cities concentrated 64% of the identified positions. Approximately 60% of registries occurred in the private sector, and specialized private establishments in the Southeast of the main actuation sites of physiotherapists, 57% of registries were linked to Specialized Ambulatory Care and 30% to Hospital Care. The Primary Health Care (PHC), which represents the priority level of attention of the health system, focused only 13% of registries, divided into 46.7% of the cities - the highest percentage in small cities (38.2% of registries in the APS). From this fact, the fourth article aimed to investigate the role of physiotherapists in APS, developed through a questionnaire online; 34 physiotherapists participated in the study, with aged between 22 and 47 years (mean 32.5 ± 6.36). Despite the intense demand for therapeutic actions, the initiatives in health promotion and disease prevention have been demonstrated. Main difficulties cited: demand spontaneous excessive, insufficient number of physiotherapists, inadequate physical space, lack of transportation to home care activities, insufficient support of medium and high complexity, ignorance of the attributions of professional PHC, difficulties in teamwork and low population adherence interventions.
Keywords: Fisioterapia; Saúde pública; Atenção primária à saúde; Sistema de saúde; Assistência hospitalar; Setor privado; Assistência ambulatorial; Physical Therapy; Public Health; Private Sector; Primary Health Care; Ambulatory Care; Hospital Care; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL